Research of a modern communicative discourse of users of the Internet network within the reflexive activity and structural theory of communicative action of Jurgen Habermas - A. Gostev; O. Belous (Цифровая социология, 2019)
A digital era with inevitability raises for us a question of need of definition of determination of the changes, resulting from informatization: processes of transformation of contents, organizational and technological bases and also valuable sense of social communications in virtual space within concepts of “open society”, “network society”, “digital society”. In article views of the reflexive activity and structural theory of communicative action of Jurgen Habermas have been revealed: “the vital world” to which “the system world” resists has been considered. An approach to knowledge of process of evolution through attraction of the typology of communicative actions, developed by Jurgen Habermas, according to which the first type of actions focused on success, and the second type – on understanding, has been described. A modern communicative discourse of users of Internet network has been analyzed, in particular, fragmentation of ordinary consciousness and colonization has been noted by its systems, which is connected with disintegration of a common understanding of the vital worlds. On the basis of the analysis of results of a research of interaction of subjects of the digital communications, carried out by the State university of management, possibilities of interpretation of primary data on the basis of scientific approach of Jurgen Habermas have been introduced. So, for example, it has been shown, that young people actively make habitable “the system world” of virtual space, replacing with it real communications and transforming real forms of behavior of “the vital world”, a certain rationality of young people at assessment of objectivity of information Internet resources is noted, their ability to define “a discourse, that is the argument” in favor of these or those forms of use of opportunities of Internet network. Ways of fuller inclusion in the modern scientific device of digital sociology of approaches of Jurgen Habermas have been offered.